World economy and international business theories, trends, and challenges - Bulatov, Alexander
This textbook offers a comprehensive picture of the world economy, the global business environment, and international business. The book is divided into three parts, the first of which introduces readers to the essentials of the world economy, including its typology, key concepts and theories, the dynamics of the world economy, and key actors and institutions. It also addresses macroeconomic and financial indicators for economic growth and forecasting and discusses major modern trends and problems, such as the Fourth Industrial Revolution, patterns of globalization, shifts in global economic power, and developmental, social and environmental challenges. In turn, the second part focuses on the global business environments, presenting country and regional studies. The third part addresses macro and micro aspects of international business, featuring contributions on topics such as global economic governance, global capital flows, multinational corporations, global value chains, international trade and its regulation and practice, international knowledge transfer, international labor migration as well as foreign aid, external debt, and business culture in international business.